Design Study of DC-DC Fractional-Order Boost-Converter using Fractional-Capacitor - Swain, Sumit; Mohapatra, Deepamjyoti; Tripathy, Madhab Chandra; Behera, Sribatsa (2022 IEEE 7th International conference for Convergence in Technology (I2CT), 2022)
In this paper, Fractional-order DC-DC Boost converter is modelled mathematically and designed in MATLAB (Simulink). Here, the duty-cycle of the boost-converter is varied from 45% to 50% for an input voltage of 1 v, where a maximum output voltage was observed at 95% duty-cycle. Then the classical capacitor in the Proposed boost converter is replaced with its fractional-order counterpart. Now, the simulated analysis of fractional-order boost converter is carried-out for fractional-order (α) from 0.2 to 1.0 using the RC-Symmetric approximated fractional-capacitor model. The output-voltage waveforms were obtained for each order of α (0.2 to 1.0) at different duty-cycle percentage (50% to 90%) and compared.